2022
DOI: 10.1111/1744-7917.13034
|View full text |Cite
|
Sign up to set email alerts
|

Testing the systematic status of Homalictus and Rostrohalictus with weakened cross‐vein groups within Halictini (Hymenoptera: Halictidae) using low‐coverage whole‐genome sequencing

Abstract: The halictid genus Lasioglossum, as one of the most species-rich bee groups with persistently contentious subgeneric boundaries, is one of the most challenging bee groups from a systematic standpoint. An enduring question is the relationship of Lasioglossum and Homalictus, whether all halictine bees with weakened distal wing venation comprise one or multiple genera. Here, we analyzed the phylogenetic relationships among the subgroups within Lasioglossum s.l. based on thousands of single-copy orthologs and ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…Entomobryomorpha [30], and Hemiptera [53]; but also in some low-level lineages Halictini [54], Membracoidea [55] and Chrysopidae [29]. In this study, 8 coalescent datasets with higher parsimony information sites yielded 24 phylogenetic trees with high branch supports (Table 2, Additional file 2: Figure S1-S24).…”
Section: Data Effectiveness and Tree Topology Robustnessmentioning
confidence: 64%
See 1 more Smart Citation
“…Entomobryomorpha [30], and Hemiptera [53]; but also in some low-level lineages Halictini [54], Membracoidea [55] and Chrysopidae [29]. In this study, 8 coalescent datasets with higher parsimony information sites yielded 24 phylogenetic trees with high branch supports (Table 2, Additional file 2: Figure S1-S24).…”
Section: Data Effectiveness and Tree Topology Robustnessmentioning
confidence: 64%
“…Benchmarking universal single-copy orthologs (BUSCOs) are a set of conservative benchmarking genes of universal single-copy orthologs identified using OrthoDB [25], which are commonly used for quantitative assessment of genome assembly and annotation completeness based on evolutionarily informed expectations of gene content [26, 27]. The potential of BUSCOs is further explored to downstream phylogenetic inference [26], whose effectiveness with high branch supports is tested and verified not only in diverse high-level lineages, such as insects [50], yeasts [51] and spiders [52], Entomobryomorpha [30], and Hemiptera [53]; but also in some low-level lineages Halictini [54], Membracoidea [55] and Chrysopidae [29]. In this study, 8 coalescent datasets with higher parsimony information sites yielded 24 phylogenetic trees with high branch supports (Table 2, Additional file 2: Figure S1-S24).…”
Section: Discussionmentioning
confidence: 99%
“…Different topologies between BI and ML trees indicated that the phylogenetic relationships based on mitogenomes among this group were still erratic, i.e., the systematic position of Stictochironomus , and the trees which were inferred by the heterogeneity model (CAT + GTR) were also not well supported. Therefore, we need to await further taxonomic and phylogenomic studies with more taxon sampling and availably molecular markers, such as ultra-conserved elements and single-copy orthologous genes, which have been successfully used in other insect groups [ 47 , 48 , 49 ] to explore the evolutionary history of the Polypedilum generic complex.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenomics has been successfully applied to phylogenetic studies of various arthropod taxa on levels ranging from order to species (Bossert et al, 2019; Bradford et al, 2022; Buenaventura et al, 2021; Johnson et al, 2022; Stephen. et al, 2017; Yu et al, 2022; Zhang et al, 2022). Moreover, it has been employed in population genomics (Winker et al, 2018).…”
Section: Discussionmentioning
confidence: 98%